Clinical-imaging complementarity in traumatic brain injury: beyond the Glasgow scale - Castell-Martínez, Leonardo Manuel; Correa-Rodríguez, José Grabiel; Fleitas-Almirall, Alejandro Antonio (Revista Científica Estudiantil de Ciencias Médicas de Matanzas, 2026)
The Glasgow Coma Scale (GCS) is useful, but it does not characterize the anatomical extent of intracranial injury in traumatic brain injury (TBI). The Marshall classification, based on CT findings, categorizes structural severity. An inverse correlation exists between the two, though it is neither linear nor deterministic. Evidence indicates that the Marshall classification primarily predicts the need for acute surgical intervention, rather than long-term functional outcomes. Consequently, the complementary relationship between the GCS and the Marshall classification is not a simple arithmetic sum, but rather a two-dimensional decision matrix. Discrepancy between the two scales—rather than concordance—generates the most clinically relevant alerts, such as in intoxicated patients or those with severe trauma and a normal CT scan. Certain limitations are acknowledged: the Marshall classification does not assess diffuse axonal injury, and its predictive power regarding functional outcomes is limited. In conclusion, the management of traumatic brain injury benefits from integrating the GCS (functional) and the Marshall classification (structural), wherein any discrepancy serves as the primary warning signal.